Evaluation of biodiversity benefits of proposed marine protected areas from the Sea Change—Tai Timu Tai Pari Hauraki Gulf Marine Spatial Plan. Issue 10 (8th September 2022) - Tablada, Jordi; Geange, Shane; Lundquist, Carolyn J.
Abstract: The Sea Change—Tai Timu Tai Pari Hauraki Gulf Marine Spatial Plan is New Zealand's first marine spatial plan and represents a collaborative response from mana whenua, local stakeholders, and regional and national governmental agencies to the threats and stressors responsible for the declining natural state of the Hauraki Gulf ecosystems. From a biodiversity perspective, the main objectives of the plan are the recovery of depleted fishing stocks and the restoration of degraded marine habitats through a network of marine protected areas (MPAs), including highly protected areas that allow for customary practices. While some information on biodiversity, resource activities, and management layers was used to develop the MPA network proposals, they were developed without benefit of systematic conservation planning tools. Here, systematic conservation planning software was used to assess the conservation benefits of different no‐take MPA network proposals, using available biodiversity and habitat datasets. The analysis indicates that while the proposed MPAs provide protection for some biodiversity features that were identified by the stakeholders, the inclusion of newly available biodiversity datasets under a systematic conservation planning approach could improve conservation outcomes. Abstract : The Sea Change—Tai Timu Tai Pari Hauraki Gulf Marine Spatial Plan is New Zealand's first marine spatial plan. Here, we show how the application of systematic conservation planning can improve conservation outcomes for this marine spatial planning process.